The secret of cycling - van Dijk, H.; van Megen, R.; Vroemen, R. (Meyer & Meyer Sport (UK) Ltd., 2017)
How much power does your human engine have? How much power do you need for cycling in different conditions? How can you optimize your training and racing performance? How can you use power meters to improve your results? What are the ultimate limits of human performance?